Harmonization of Islamic Law and Local Culture: A Study of Indonesian Sundanese Ethnic Culture - Muhammad Shuhufi; Arip Purkon (IAIN Manado, 2023)
This study analyzed the application of Islamic law in the Sundanese ethnic community and explored the relationship between Sundanese social life and Islamic law. This research is qualitative research with a case study approach. The collection of data was obtained through observation and documentation. Data is described systematically and objectively, then analyzed using the content analysis method. This study concluded that acculturation and assimilation between the structure of Sundanese society and Islamic law had formed a unique characteristic of Sundanese society. It can occur because the reality of Sundanese people who have accepted Islam is due to harmony with Sundanese values. This research can be used as a model for building a harmonious relationship between Islamic law and the social structure of society. Islamic law can be applied without damaging the social structure of society. Culture, social structure, and Islamic law can be applied harmoniously. This study provided an empirical example of a harmonious relationship between the social structure of society and the application of Islamic law. Both can run simultaneously without eliminating each other.